Specificity of plant-microbe interactions in the tree mycorrhizosphere biome and consequences for soil C cycling - Churchland, Carolyn; Grayston, Sue J. (Frontiers in Microbiology, 2014)
Mycorrhizal associations are ubiquitous and form a substantial component of the microbial biomass in forest ecosystems. Some 10,000 species of ectomycorrhizal fungi are currently recognized, some of which are host specific and will only associate with a single tree species, for example, Suillus grevillei with larch. Mycorrhizae are a strong sink for plant C; differences in mycorrhizal anatomy, particularly the presence and extent of emanating hyphae, can affect the amount of plant C allocated to these assemblages and results in qualitative and spatial variations in soil nutrient availability and acquisition. Mycorrhizal morphology affects not only spatial distribution of C in forests, but also differences in the longevity of these diverse structures have important consequences for C sequestration in soil. Through new genomic techniques we are beginning to understand the mechanisms involved in the specificity and selection of ectomycorrhizal associations, though much less is known about arbuscular mycorrhizal associations. In this review we examine evidence for tree species- mycorrhizal specificity, the mechanisms involved (e.g. signal compounds). We also explore what is known about the effects of these associations and interactions with other soil organisms on the quality and quantity of C flow into the mycorrhizosphere (the area under the influence of mycorrhizal root tips), including spatial and seasonal variations. The enormity of the mycorrhizosphere biome in forests and its potential to sequester substantial C belowground points to the vital knowledge gap on the dynamics of the different mycorrhizal functional groups in diverse forests.